Energy-saving and environment-friendly building interior material and preparation method thereof

By improving the composition and processing technology of honeycomb curtain materials and adding ingredients such as hollow glass microspheres and water-repellent agents, the problems of existing materials that are difficult to clean and have poor filtration performance are solved, achieving more efficient heat insulation, easy decontamination and air conditioning. The filtering effect promotes building energy conservation and environmental protection.

CN119332515APending Publication Date: 2025-01-21XINLONG HLDG (GRP) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411446402.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The existing honeycomb curtain materials are not easy to clean and have poor filtration of air pollutants, which can cause environmental pollution and waste of energy consumption.

Method used

Polyester fiber is used as raw material, and after opening, carding, spunlace, and drying treatments, functional finishing liquid is added, including adhesives, hollow glass microspheres, water-repellent agents and other ingredients, and is processed through padding, coating, printing, etc. It is applied to the base fabric to form a building interior material with heat insulation, easy decontamination and air filtration properties.

Benefits of technology

The material's thermal insulation performance, easy decontamination performance and air filtration performance are improved, energy consumption is reduced, the service life of the material is extended, and environmental pollution is reduced.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses an energy-saving and environment-friendly building interior material which comprises base cloth with the gram weight of 30-100g / m < 2 >. Comprising the following components in percentage by weight: 5-20% of an adhesive, 0.1-0.3% of a dispersing agent, 0.1-0.3% of a defoaming agent, 0.1-0.3% of a whitening agent, 0.5-1.0% of a thickening agent, 1-20% of hollow glass microspheres and the balance of water, wherein the hollow glass microspheres can improve the stiffness and the reflectivity of the material and have a heat insulation effect. The hollow glass microspheres with low heat conductivity coefficient and high reflectivity are used as the filler, so that on one hand, the stiffness of the material can be improved, and the cord fabric has better folding formability; on the other hand, the high reflectivity of the hollow glass microspheres is utilized, so that the irradiated sunlight can be reflected as much as possible, and the energy absorbed by the curtain cloth is reduced; the low heat conductivity coefficient can achieve a certain heat insulation effect, and temperature rise of the curtain cloth is slowed down. On the basis, the use of the water repellent endows the cord fabric material with good soil release performance, does not absorb water, does not deform, and does not affect the normal use of the cord fabric after being wiped.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of nonwoven fabrics, and more specifically, to an energy-saving and environment-friendly building interior material and a preparation method thereof. Background Art

[0002] Energy consumption is one of the main problems facing mankind in the 21st century. Room cooling and heating account for the majority of residential and commercial energy consumption. my country's building energy consumption accounts for 45.9% of the total social energy consumption, of which building energy consumption includes energy consumption in the building use phase, energy consumption in the building construction phase and energy consumption in the building production phase. The energy consumption in the building use phase, that is, the building operation energy consumption, includes people's daily energy consumption, such as heating, air conditioning, lighting, cooking, laundry and other energy consumption, accounting for 21.2% of the total social energy consumption. In the building operation energy consumption, the energy lost through doors and windows accounts for 45% to 50% of the building operation energy consumption. Therefore, reducing the energy loss through doors and windows in a reasonable way is of great significance to achieving building energy conservation.

[0003] Honeycomb blinds, whose design is inspired by honeycombs, are window decoration materials with a certain hollow structure developed using bionics. Their unique hollow structure utilizes the lower thermal conductivity of air to provide thermal insulation. When used in the field of building interiors, they can effectively reduce energy loss through doors and windows, providing a new direction for building energy conservation.

[0004] Currently, conventional honeycomb blinds are not easy to clean. After absorbing dust or getting stained, they can only be replaced as a whole, which not only causes waste but also brings a burden to the environment. In addition, the base material of honeycomb blinds is mainly made of spunlace non-woven fabrics, which are characterized by large pores and have basically no filtering effect on air pollutants.

[0005] As domestic and foreign consumers' awareness of energy conservation, environmental protection, health and safety increases, and the concept of sustainable development becomes more popular, how to further improve the practicality of cellular blinds has become a key issue that people in this field need to solve. Summary of the invention

[0006] The main purpose of the present invention is to improve the thermal insulation, decontamination and filtering performance of interior decoration materials by improving the material components in view of the above defects and shortcomings. Based on this, an energy-saving and environmentally friendly building interior decoration material is provided.

[0007] Another object of the present invention is to provide a method for preparing energy-saving and environmentally friendly building interior materials.

[0008] In order to achieve the above object, the specific technical solution adopted by the present invention is:

[0009] The energy-saving and environmentally friendly building interior material of the present invention adopts polyester fiber as raw material, and obtains base fabric through opening, carding, spunlacing and drying, and the base fabric has a gram weight of 30-100g / m2 The base fabric is functionally finished. The finishing liquid includes: 5-20% adhesive, 1-20% hollow glass microspheres, 0.1-0.3% dispersant, 0.1-0.3% defoamer, 0.1-0.3% brightener, 0.5-1.0% thickener, 0.5-3.0% water repellent, and the rest is water. The finishing methods include padding, coating, and printing. The amount of liquid is 80%-300% of the weight of the base fabric, and the dry weight of the liquid is 10-30g / m 2 .

[0010] Preferably, the adhesive is one or more of acrylic latex, styrene-acrylic latex, styrene-butadiene latex, polyurethane latex, and polyvinyl alcohol.

[0011] Preferably, the hollow glass microspheres are made of borosilicate and have a particle size of 10-30 um.

[0012] Preferably, the dispersant is a sodium salt of polycarboxylate.

[0013] Preferably, the defoaming agent is polydimethylsiloxane.

[0014] Preferably, the brightener is a nonionic oxazole derivative.

[0015] Preferably, the thickener is an acrylic acid copolymer.

[0016] Preferably, the water repellent is one or more of a silicone water repellent, a wax composition, and a polyacrylate water repellent.

[0017] The method for preparing the energy-saving and environmentally friendly building interior material of the present invention comprises:

[0018] 1. Open, card, spunlace and dry the polyester fiber to obtain a base fabric, wherein the polyester fiber is ordinary polyester fiber or whitening polyester fiber, and the base fabric has a gram weight of 30-100 g / m 2 .

[0019] 2. Prepare functional finishing liquid, weigh enough water, add 5-20% adhesive, 0.1-0.3% dispersant, 1-20% hollow glass microspheres, 0.1-0.3% defoamer, 0.1-0.3% brightener, 0.5-1.0% thickener, 0.5-3.0% water repellent in sequence, stir well for use.

[0020] 3. Apply the prepared functional finishing liquid to the base fabric, and the application method includes padding, coating, and printing.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] 1. Using hollow glass microspheres with low thermal conductivity and high reflectivity as fillers can, on the one hand, improve the stiffness of the material and make the curtain have better folding formability; on the other hand, by utilizing the high reflectivity of hollow glass microspheres, as much sunlight as possible can be reflected to reduce the energy absorbed by the curtain; the low thermal conductivity can have a certain insulation effect and slow down the increase in the temperature of the curtain.

[0023] 2. The use of brighteners can convert the ultraviolet light absorbed by the cloth into blue or blue-purple visible light, which is mixed with the yellowish light on the cloth to emit white light, thereby reducing the ultraviolet light energy absorbed by the cloth and improving the weather resistance of the material.

[0024] 3. The use of water repellent gives the curtain material good decontamination properties. When the fabric absorbs dust or is stained, you can directly wipe it with a wet cloth or rinse the surface of the curtain with water to make the curtain clean as new. The fabric surface remains dry, does not absorb water, does not deform, and does not affect the normal use of the curtain.

[0025] 4. This material has a certain air filtration effect and can effectively block pollutants such as dust and pollen with a minimum particle size of 5um. DETAILED DESCRIPTION

[0026] The present invention is further explained and illustrated by specific implementation modes below. It should be understood that the purpose of the following implementation modes is to make the technical solution of the present invention clearer and easier to understand, and does not limit the protection scope of the claims.

[0027] The present invention will be further described below by means of specific examples.

[0028] Example 1

[0029] 1. Open, card, spunlace and dry the polyester fiber to obtain a base fabric, wherein the polyester fiber is ordinary polyester fiber and the base fabric has a gram weight of 30 g / m 2 .

[0030] 2. Prepare 1000 kg of functional finishing liquid, weigh 77.2% of water in proportion, add 20% of adhesive (acrylic latex), 0.1% of dispersant, 1% of hollow glass microspheres, 0.1% of defoamer, 0.3% of brightener, 0.8% of thickener, 0.5% of water repellent (silicone waterproofing agent) in sequence, stir well and set aside.

[0031] 3. Apply the prepared functional finishing liquid to the base fabric by coating, with the amount of liquid applied being 300% and the dry weight of the liquid being 10g / m 2 .

[0032] Example 2

[0033] 1. Open, card, spunlace and dry the polyester fiber to obtain a base fabric, wherein the polyester fiber is a whitening polyester fiber and the base fabric has a gram weight of 100 g / m 2 .

[0034] 2. Prepare 1000 kg of functional finishing liquid, weigh 55.3% of water in proportion, add 20% adhesive (styrene acrylic latex), 0.3% dispersant, 20% hollow glass microspheres, 0.3% defoamer, 0.1% brightener, 1.0% thickener, 3.0% water repellent (wax composition) in sequence, stir well for use.

[0035] 3. Apply the prepared functional finishing liquid to the base fabric. The application method is printing. The amount of liquid applied is 100%, and the dry weight of the liquid is 30g / m 2 .

[0036] Example 3

[0037] 1. Open, card, spunlace and dry the polyester fiber to obtain a base fabric, wherein the polyester fiber is ordinary polyester fiber and the base fabric has a grammage of 80 g / m2.

[0038] 2. Prepare 1000 kg of functional finishing liquid, weigh 80.4% of water in proportion, add 5% adhesive (polyurethane latex), 0.2% dispersant, 12% hollow glass microspheres, 0.2% defoamer, 0.2% brightener, 0.5% thickener, 1.5% water repellent (polyacrylate water repellent), stir well and set aside.

[0039] 3. Apply the prepared functional finishing liquid to the base fabric by padding, with the liquid volume of 80% and the dry weight of the liquid being 10g / m 2 .

[0040] Comparative Example 1

[0041] 1. Open, card, spunlace and dry the polyester fiber to obtain a base fabric, wherein the polyester fiber is a common polyester fiber and the base fabric has a gram weight of 80 g / m 2 .

[0042] 2. Prepare 1000 kg of functional finishing liquid, weigh 81.6% of water in proportion, add 5% adhesive (polyurethane latex), 0.2% dispersant, 12% hollow glass microspheres, 0.2% defoamer, 0.2% brightener, 0.8% thickener in sequence, stir well and set aside.

[0043] 3. Apply the prepared functional finishing liquid to the base fabric by coating, with the amount of liquid applied being 150% and the dry weight of the liquid being 17g / m 2 .

[0044] Comparative Example 2

[0045] 1. Open, card, spunlace and dry the polyester fiber to obtain a base fabric, wherein the polyester fiber is a common polyester fiber and the base fabric has a gram weight of 80 g / m 2 .

[0046] 2. Prepare 1000 kg of functional finishing liquid, weigh 82.1% of water in proportion, add 15% adhesive (polyurethane latex), 0.2% dispersant, 0.2% defoamer, 0.2% brightener, 0.8% thickener, 1.5% water repellent (polyacrylate water repellent) in sequence, stir well and set aside.

[0047] 3. Apply the prepared functional finishing liquid to the base fabric by coating, with the amount of liquid applied being 150% and the dry weight of the liquid being 10g / m 2 .

[0048] Implementation effect:

[0049] (1) Filtration efficiency: Single-piece material test, using Shichen SC-FT-1406D automatic filter material tester, sodium chloride particles, flow rate 32L / min, filtration efficiency test as follows:

[0050] Sodium chloride particle size 1.0um 3.0um 5.0um Example 1 27.3% 27.3% 99.9% Example 2 33.3% 33.4% 99.9% Example 3 28.9% 28.9% 99.9% Comparative Example 1 28.6% 28.7% 99.9% Comparative Example 2 27.3% 27.4% 27.4%

[0051] (2) Preparation of honeycomb material: Cut the material into a single piece of 5.2 cm in width, fold it inward 2.6 cm from each side in the horizontal direction, and stick the two sides with a double-sided tape with a width of 0.5 cm. The adhesive part is bonded to the back of the next folded sample. During the test, the sample is unfolded into a honeycomb shape. The test box is handmade, with a hole opened on the top of the black paper box. The photovoltaic sensor is placed inside the box, 3 cm vertically away from the hole. During the test, the sample unfolded into a honeycomb shape completely covers the hole of the black paper box, and the solar radiation energy value is read. The results are as follows:

[0052] <![CDATA[Solar irradiance W / m 2 > Folding molding effect No sample occlusion 800 / Example 1 165 The sample is slightly stiff and is not easily deformed after folding. Example 2 103 The sample is stiff and not easily deformed after folding Example 3 113 The sample is stiff and not easily deformed after folding Comparative Example 1 115 The sample is stiff and not easily deformed after folding Comparative Example 2 170 The sample is soft and easy to change shape after folding

[0053] (3) Water repellency: Rinse the honeycomb material under the tap for 10 seconds, take it out and observe its ability to remove dirt. The results are as follows:

[0054] Easy to remove stains Example 1 The surface is dry, with slight water marks remaining Example 2 The surface is dry, with slight water marks remaining Example 3 The surface is dry, with no water residue Comparative Example 1 The cloth is wet Comparative Example 2 The surface is dry, with no water residue

[0055] According to the implementation results, it can be seen that the addition of hollow glass microspheres has a beneficial effect on the folding formability of the material, blocking solar radiation energy, and the filtration efficiency of 5um particle size particles. The addition of water repellent can effectively improve the material's ability to remove dirt and improve the material's durability.

[0056] The present invention is described by way of embodiments, but does not constitute a limitation to the present invention. With reference to the description of the present invention, other changes to the disclosed embodiments are easily conceivable to professionals in the field, and such changes should fall within the scope defined by the claims of the present invention.

Claims

1. An energy-saving and environmentally friendly building interior material, characterized by: Including base fabric, the base fabric weight is 30-100g / m 2 ; The invention comprises a finishing liquid applied to a base fabric, wherein the finishing liquid comprises by weight: 5-20% adhesive, 0.1-0.3% dispersant, 0.1-0.3% defoamer, 0.1-0.3% brightener, 0.5-1.0% thickener, 1-20% hollow glass microspheres which can improve the stiffness and reflectivity of the material and have a heat insulation effect, and the rest is water.

2. The energy-saving and environmentally friendly building interior material according to claim 1, characterized in that: The hollow glass microspheres are made of borosilicate.

3. The energy-saving and environmentally friendly building interior material according to claim 1, characterized in that: The particle size of the hollow glass microspheres is 10-30 μm.

4. The energy-saving and environmentally friendly building interior material according to claim 1, characterized in that: The finishing liquid also includes a water repellent.

5. The energy-saving and environmentally friendly building interior material according to claim 4, characterized in that: The water repellent is one or more of an organic silicon water repellent, a wax composition, or a polyacrylate water repellent.

6. The energy-saving and environmentally friendly building interior material according to claim 1, characterized in that: The adhesive is one or more of acrylic latex, styrene-acrylic latex, styrene-butadiene latex, polyurethane latex, or polyvinyl alcohol; The dispersant is a sodium salt of polycarboxylate; The defoaming agent is polydimethylsiloxane; The brightener is a nonionic oxazole derivative; The thickener is an acrylic acid copolymer.

7. The energy-saving and environmentally friendly building interior material according to claim 1, characterized in that: The base fabric is made of polyester fiber, and the polyester fiber includes whitening polyester fiber.

8. A method for preparing the energy-saving and environmentally friendly building interior material according to any one of claims 1 to 7, characterized in that: Step 1: opening, combing, spunlacing and drying the polyester fibers to obtain a base fabric; Step 2: Prepare finishing liquid: weigh enough water, add 5-20% adhesive, 0.1-0.3% dispersant, 1-20% hollow glass microspheres, 0.1-0.3% defoamer, 0.1-0.3% brightener, 0.5-1.0% thickener, 0.5-3.0% water repellent in sequence, stir well for use. Step 3: Apply liquid: Apply the prepared finishing liquid to the base fabric.

9. The method for preparing the energy-saving and environment-friendly building interior material according to claim 8, characterized in that: The liquid application method includes padding, coating, or printing.

10. The method for preparing the energy-saving and environment-friendly building interior material according to claim 8, characterized in that: The dry weight of the upper liquid is 10-30 g / m 2 .